Media edukasi kerohanian Kristen tentang gembala dan domba tersesat berbasis game 3D - Omega, Yuseva Kristine; Susilo, Dahlan; Retnoningsih, Dwi (Universitas Merdeka Malang, 2023)
It is hoped that this Shepherd and Sheep Game can provide insight and knowledge about the depiction of God's love through the parable of sheep and shepherds and help Christian youths learn and understand Christianity. The making of this game uses the Unity 3D game engine and uses the C# programming language. This research uses the waterfall method as a system development method. The data collection methods used in this research are observation, interviews, and literature study. In the Shepherd and the Lost Sheep Game, there are four levels which have missions that must be completed by the player. The testing method uses Blackbox and Beta Testing. Based on the results of blackbox testing, overall this game has been successfully created and functions well. Based on the results of beta testing using a questionnaire distributed to 30 users, a score of 951 was obtained with a percentage value of 79.25%. It can be concluded that overall users feel satisfied after playing the Shepherd and the Lost Sheep game both in terms of system and material, and users feel quite helped in understanding Christian spiritual material by playing this game.